PROSPECTS FOR THE DEVELOPMENT OF MEDICAL INSTITUTIONS UNDER THE CONDITIONS OF HEALTH REFORM - Vasilyev, A.H.; Mykhalchuk, V.M.; Hbur, Z.V.; Voronenko, Yu.V. (World of Medicine and Biology, 2019)
The article systematizes the key results of the reform of the health sector. It is established that reforms will lead to an increase in the level of competition in the field of medicine, which will require private clinics to optimize their work. It is proved that the implementation of reforms leads to the development of private medicine, which today a number of competitive advantages has compared to state health facilities: the quality of medical services, equipment, and a wide range of treatment and diagnosis of diseases, highly specialized personnel, and the ability to provide continuous training of staff. The key areas of optimization of the work of private clinics are identified: the establishment of cooperation with contractors of a private clinic; optimization of work of personnel, selection of personnel and formation of teams, payment of their work in accordance with the legislation; technical and technological support of the activity of a private clinic, which involves compliance of equipment and premises with the existing legal standards; automated laboratory diagnostic methods that can provide high performance; integration of information systems with state-owned electronic health services.
Keywords: reforms; health care; private clinics; private medicine; medical institutions